A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
Using the completingthesquare method, rewrite f(x) = x2 − 6x + 2 in vertex form.
anonymous
 one year ago
Using the completingthesquare method, rewrite f(x) = x2 − 6x + 2 in vertex form.

This Question is Closed

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0f(x) = x²  6x + 2 f(x)  2 = x²  6x f(x)  2 + 9 = x²  6x + 9 f(x) + 7 = (x  3)² f(x) = (x  3)²  7 Could you please fan me?

SolomonZelman
 one year ago
Best ResponseYou've already chosen the best response.0this is against the rules, and should be agains your conscience as well (if you got one)

DanJS
 one year ago
Best ResponseYou've already chosen the best response.0don't just give solutions, help the person along prolly

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0thank you anyway tho aha

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0f(x) = x²  6x + 2 f(x)  2 = x²  6x f(x)  2 + 9 = x²  6x + 9 f(x) + 7 = (x  3)² f(x) = (x  3)²  7 Those are the steps!
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.